2017
DOI: 10.1038/ismej.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Microbial shifts and signatures of long-term remission in ulcerative colitis after faecal microbiota transplantation

Abstract: Faecal microbiota transplantation (FMT) may contribute towards disease remission in ulcerative colitis (UC), but it is unknown which factors determine long-term effect of treatment. Here, we aimed to identify bacterial signatures associated with sustained remission. To this end, samples from healthy donors and UC patients-grouped into responders and non-responders at a primary end point (week 12) and further stratified by sustained clinical remission and relapse assessed at ⩾1-year follow-up were analysed, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(190 citation statements)
references
References 51 publications
7
177
1
5
Order By: Relevance
“…The inflamed mucosa showed fewer Firmicutes (eg, Enterococcus ) and more Proteobacteria (eg, Escherichia – Shigella ) than healthy controls . Patients with UC had fewer bacteria isolated from the Clostridium cluster XIVa , and a significantly increased number of Bacteroidetes . In another study, sulfate‐reducing bacteria, which may proliferate with the release of toxic sulfide, were the dominant microflora in UC, but they were in fewer in healthy individuals ) .…”
Section: Ecological Imbalance Of Intestinal Flora In Ucmentioning
confidence: 91%
See 1 more Smart Citation
“…The inflamed mucosa showed fewer Firmicutes (eg, Enterococcus ) and more Proteobacteria (eg, Escherichia – Shigella ) than healthy controls . Patients with UC had fewer bacteria isolated from the Clostridium cluster XIVa , and a significantly increased number of Bacteroidetes . In another study, sulfate‐reducing bacteria, which may proliferate with the release of toxic sulfide, were the dominant microflora in UC, but they were in fewer in healthy individuals ) .…”
Section: Ecological Imbalance Of Intestinal Flora In Ucmentioning
confidence: 91%
“…However, patients who did not react were observed to have elevated numbers of Fusobacterium gonidiaformans , Sutterella wadsworthensis and Escherichia coli , as well as enhanced heme and lipopolysaccharide biosynthesis. One study showed that the sustained remission in UC could be associated with a recovery of butyrate production capacity . The major factors of FMT that are associated with clinical improvement include the diversity and abundance of Eubacterium hallii in the colonized microflora, the similarity of the metabolomics and virus omics profiles to those of the donor and the concentration of fecal metabolites …”
Section: Therapeutic Strategy Of Fmt In Uc and Controversymentioning
confidence: 99%
“…1.4 deviations above other donors). Higher butyrate levels have been associated with a higher microbial diversity and better therapeutic response rates in previous FMT trials in patients with recurrent clostridium difficile infection, UC, or metabolic syndrome [22-25]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased microbial diversity has been associated with recurrent Clostridium difficile infection (RCDI) (Milani et al ., 2016). Changes in the abundance of the butyrate‐producing bacterial community along with reduced butyrate formation were observed in inflammatory bowel disease (IBD) (Sokol et al ., 2009; Kumari et al ., 2013; Fuentes et al ., 2017). To restore the microbial balance, transfer of faecal microbiota from a healthy donor (FMT) to diseased patients has been suggested as a therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate is an important short‐chain fatty acid (SCFA) that provides several benefits to the host (Tan et al ., 2014). Butyrate producers of the Clostridium clusters IV and XIVa have been associated with a ‘sustained response’ to FMT in IBD and could therefore be crucial in restoring the metabolic balance of a disturbed intestinal microbiota (Fuentes et al ., 2017). In this study, three different colonic microbiota, originating from two in vitro gut fermentations inoculated with immobilized faecal microbiota of two healthy adult donors, were preserved in buffers containing either glycerol or inulin or a combination thereof.…”
Section: Introductionmentioning
confidence: 99%